Socioeconomic, Psychological, and Informational Dynamics in Shaping American Public Opinion Perceptions on Climate Change. - Ugwuoke, Jude Chukwuebuka (International Journal of Multidisciplinary Sciences and Arts, 2024)
Climate change remains one of the most pressing challenges of the 21st century, invoking a wide spectrum of public opinions and attitudes. In the United States, sociopolitical, economic, and educational factors influence the public's perception of climate change and its science. This study examines the complexities of American public opinion on climate change by analyzing the relationship between various socio-demographic variables and three specific perceptions: belief in the occurrence of climate change, support for a carbon tax, and the convincingness of climate science. Utilizing logistic and linear regression models on survey data, this study identifies significant predictors for each climate change perception metric. The results indicate that political party affiliation, particularly Republican identification, is inversely related to the belief in climate change and the persuasiveness of climate science. Conversely, educational attainment correlates positively with the belief in climate change and support for carbon taxation, suggesting that higher education levels foster greater acceptance and proactive attitudes towards climate policy. Gender analysis revealed that males are less inclined to find climate science convincing, highlighting the need for gender-sensitive communication strategies. Interestingly, regional factors showed negligible influence on climate change perceptions, challenging common assumptions about geographical determinants. This study contributes to the discourse on environmental policy and public engagement by delineating the demographic contours of climate change belief systems in the U.S., offering insights for targeted educational and communication strategies to bridge the ideological divide and enhance public consensus for climate action.